Profitability of blantic cattle traders as a supply chain institution in Minahasa Regency, Indonesia - Osak, Richard E.M.F; Rundengan, Meiske L.; Pangemanan, Stevy P.; Tulung, Yohannis L.R.; Durandt, R.R. (International Journal of Environment, Agriculture and Biotechnology, 2021)
The blantic cattle traders as a supply chain institution in Indonesia play a role in the task of marketing cattle from farmer in the villages to buyers of cattle at the blantic cattle market. This research aims to study the profitability of blantic cattle traders in Minahasa Regency, Indonesia. The data were obtained from direct interviews with blantic cattle traders using questionnaires. The data were analyzed the factors that affect the profit with multiple linear regression. Blantic cattle traders profitability can be seen from the profit generated on profit and costs ratio (pcr) earned at 1.85% which is high. The number of cattle sold has a significant effect on the profits of blantic cattle traders, where every additional number of beef cattle sold by 1 head, the profit will increase by IDR 282,132.71, so that the more the number of cattle sold, the greater the amount of profit obtained. While age, education level, and work experience do not significantly affect the profits of blantic cattle traders. This is because the market demand for cattle tends to increase, therefore blantic cattle traders need to streamline their network with cattle farmers as a supply chain institution to maintain stock and total sales.